Promoting 4.0 Supply Chain Innovation for Fisheries Bioecoregion: A Case Study in West Java Province, Indonesia - Nurhayati, Atikah; Nurruhwati, Isni; Herawati, Titin; Riyantini, Indah; Aisah, Isah (Indonesia Academia Research Society, 2023)
The industrialization of marine and fisheries is the integration of production systems from upstream and downstream, to increase the scale and quality of production, productivity, competitiveness, and value added of fishery products. Bio-ecoregion-based fisheries and marine resources from each region, especially in West Java, which is one of the producers of fisheries and marine production through the development of industrialization innovations 4.0. This study aims to analyze how to promote 4.0 industrial innovations for Fisheries Bioecoregion, case study in West Java Province, Indonesia. The method used in this research is quantitative description, using primary and secondary data. Data analysis tools use SWOT to systematically analyze various factors based on logic that can maximize strengths and opportunities, but simultaneously can minimize weaknesses and threats. Based on the research results, the strength that is owned is to create a transformation of the potential of fishery resources to the exploitation of fishery resources based on Bioecoregion. Opportunities faced by the transformation of open market access management and high competitiveness in fisheries and marine products. The challenges faced must be able to create a digital bio-ecoregion-based fishing industry system. The threat faced by the transformation of the workforce towards digitalization. Based on the SWOT analysis being in quadrant 2 it means it is in a diversification strategy. Promoting 4.0 Industrial Innovations For a Fisheries Bioecoregion, based on: increasing the added value of fisheries industrialization, increasing the competitiveness of fishery products; strengthening of marine and fisheries industry players; commodity-based, regional, and regional management systems with a concentration on leading commodities, modernization of upstream and downstream production systems; balance between the use of natural resources and sustainable environmental protection; and changes in the mindset and behavior of modern society.